Single-cell transcriptomics reveals an angiogenic cell population for therapeutic angiogenesis in adipose tissue. (3rd October 2022) - Inoue, O; Usui, S; Goten, C; Hashimuko, D; Yamaguchi, K; Takeda, Y; Nomura, A; Ootsuji, H; Takashima, S; Iino, K; Takemura, H; Sanchez-Gurmaches, J; et al.
Abstract: Background: Therapeutic angiogenesis mediated by stem/progenitor cells is an attractive therapeutic option against cardiovascular disease (CVD). Adipose tissue (AT) can be safely obtained even in CVD patients with anti-platelet medications, and it is a readily available source of culture-expanded adipose-derived stem cells (ADSCs) for transplantation. Single-cell transcriptome enables us to screen all the surface markers at once, while conventional strategies have been limited for the number of target markers. Furthermore, gene profiling at single-cell resolution can be used for the quantification of each marker by how many favorable cells can be purified without mixing of detrimental cells. Purpose: We aimed to identify and characterize a cell population with in vivo angiogenic potential by single-cell RNA sequencing (scRNA-seq) analysis and xenograft experiments. Methods: We revisited scRNA-seq datasets of single cell fraction from AT, bone-marrow (BM), and umbilical-cord blood (UCB, n=6/organ) to find cell populations with pro-angiogenic potential. Next, we collected AT from CVD patients (n=23) and used multicolor flow cytometry to quantify and sort the specific populations. PBS, the specific marker-negative and unsorted ADSCs were used as controls. Xenograft models of PKH26 pre-labeled human ADSC transplantation in limb ischemia were used to evaluate the lectin capillary density, PKH + engrafted ADSCs, and blood flow recovery. Results: Clustering divided CD45 – CD31 – CD34 + progenitor fraction into 3 clusters. We identified pro-/anti-angiogenic clusters based on the expressions of well-known pro-/anti-angiogenic factors. All genes encoding cell-surface proteins were compared in this functional clustering, resulted in 17 markers screened (Fig. 1A, B). Taken together with enrichment analysis, CD271 + cells showed predominant and pro-angiogenic gene profile from the other top candidates including CD36 and CD54 (Fig. 1C, D). Next, we evaluated the number and gene profile of CD271 + cells in well-known stem cell sources including BM and UCB. Surprisingly, the number of CD271 expressing cells were significantly lower and did not show angiogenic gene profile in BM and UCB (Fig. 2A). In analysis of AT from 23 CVD patients, CD271 + cells were significantly decreased by donor insulin resistance (Fig. 2B). Cell therapy using CD271 + ADSCs demonstrated in vivo angiogenic capacity compared to those of CD271 – ADSCs and PBS in limb ischemia model. Furthermore, CD271 + ADSC transplantation showed enhanced efficacy compared to unsorted ADSCs from the same donors (Fig. 2C–E). Conclusion: In this study, we identified CD271 + cell population in AT as an angiogenic cell population through scRNA-seq analysis and cell therapy experiments. AT obtained from donors without insulin resistance would be the most suitable for CD271 + ADSC isolation. CD271 + ADSC transplantation with a promising angiogenic capacity could contribute better cell-based therapy tackling CVD. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Japan Society for the Promotion of Science (JSPS) KAKENHI (Tokyo, Japan)